Analysis of Problem-Based Learning Models in Mathematics Using Two Variables - Mandopa, Andi Saputra (Gayaku Publisher, 2023)
The purpose of this study was to determine the extent to which the growth of students' mathematics learning outcomes by using the Problem Based Instruction (PBI) learning model in Class VII material at the Salapiah Gunung Silayang-Layang Islamic Boarding School. school for the 2020-2021 academic year. This type of research is Classroom Action Research (AUTO), which consists of two parts. The subjects of this study were class VII students of Pondok Pesantren Salapiah Gunung Silayang Layang Padangsidimpuan for linear equations with two variables. The results showed that student learning outcomes in learning mathematics using the PBI Learning Model for students of the Salapiah Gunung Silayang-Layang Islamic Boarding School Class VII-2 in the material variable Linear Equation One academic year 2021 increased to 71.85, increasing to 71.85. category